2001
DOI: 10.1046/j.1528-1157.2001.13701r.x
|View full text |Cite
|
Sign up to set email alerts
|

Premature Ovarian Failure in Women with Epilepsy

Abstract: Summary:Purpose: Women with epilepsy (WWE) have an increased risk for several reproductive endocrine disorders that may affect their fertility. The incidence of premature ovarian failure (POF) in women with epilepsy has not been systematically studied. This study examined the incidence of POF in women with epilepsy.Methods: Fifty consecutively evaluated cognitively normal women with epilepsy, aged 38-64 years, whose seizures began before age 41 years, were interviewed for symptoms of perimenopause and menopaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 25 publications
1
43
0
7
Order By: Relevance
“…1998; Klein et al. 2001; Harden and Pennell 2013). Premature menopause in WWE has also been reported (Klein et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1998; Klein et al. 2001; Harden and Pennell 2013). Premature menopause in WWE has also been reported (Klein et al.…”
Section: Discussionmentioning
confidence: 99%
“…Premature menopause in WWE has also been reported (Klein et al. 2001). Psychosocial factors, such as difficulties in finding a partner, low self‐esteem, stigmatization, and social isolation may also play a substantial role in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…Mumps oophoritis has been considered to be a cause of POF [33]. Other reported associations are cigarette smoking and epilepsy [34, 35]. The available data regarding the effects of endocrine disruptors, heavy metals, solvents, pesticides, plastics, industrial chemicals, and cigarette smoke on female reproduction are equivocal [36].…”
Section: Autoimmune Causes Of Pofmentioning
confidence: 99%
“…Klein et al [113] reported that women with epilepsy were at higher risk for developing POI than general population. Whether education level and other sociodemographic characteristics are associated with risks of POI is inconsistent among different literatures.…”
Section: Toxins and Other Environmental/lifestyle Factorsmentioning
confidence: 99%